1993
DOI: 10.1023/a:1018973814456
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The mechanism of the topical delivery of piroxicam, a nonsteroidal antiinflammatory drug, has been controversial as to whether systemic absorption is required for topical efficacy. This study, using in vivo pigs treated with topical 3H-piroxicam gel, was designed to assess the role of systemic absorption on its delivery to deep tissues. Further, the role of the structure of the cutaneous vasculature (e.g., direct cutaneous or musculocutaneous) was studied. Finally, piroxicam delivery was measured using in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…Anyway, difference in the permeation rates of the three model drugs between YMP and human skin are probably due to differences in skin barrier function among species. 16,26,31) In the present study, the inter-and intra-individual variations in YMP skin permeability were found to be smaller than those in human skin permeability. In addition, the interand intra-regional variations in YMP skin permeability were remarkably smaller than the inter-and intra-individual variations in human skin permeability, and were similar to the inter-individual variations in SD rat skin permeability.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Anyway, difference in the permeation rates of the three model drugs between YMP and human skin are probably due to differences in skin barrier function among species. 16,26,31) In the present study, the inter-and intra-individual variations in YMP skin permeability were found to be smaller than those in human skin permeability. In addition, the interand intra-regional variations in YMP skin permeability were remarkably smaller than the inter-and intra-individual variations in human skin permeability, and were similar to the inter-individual variations in SD rat skin permeability.…”
Section: Discussioncontrasting
confidence: 59%
“…1,[17][18][19][20][21][22] It has been reported that the histological characteristics and permeability properties of pig skin closely resemble those of human skin. 6,7,[23][24][25][26][27][28] In addition, the Yucatan micropig (YMP) has been utilized for numerous research applications and has been suggested as an animal model for biomedical research because of their physiological and morphological similarity to humans. 29) In addition to its hairless feature, YMP has been reported to be similar clinical, structural, immunohistochemical and reactivity properties to human skin.…”
mentioning
confidence: 99%
“…Figure 12 shows an example of his work [95]. An important contribution is their finding that deep tissue penetration may relate to the vascularity below the site of topical application [96]. His group has also explored the predictability of solute penetration from complex vehicles [97] and worked with his wife Nancy on studies assessing the safety of nanomaterials [98,99,100,101,102].…”
Section: My Generation - the Baby Boomersmentioning
confidence: 99%
“…Most drugs are taken up by these vessels to migrate to the systemic circulation, whereas a portion is further diffused into deeper tissues such as the subcutis and muscle. 1,2) If the applied drug is a prodrug, a peptide or an oligonucleotide that can be readily metabolized in skin, its metabolism makes the skin disposition of the drug very difficult.Such dermato-pharmacokinetics have been analyzed by several in vitro and in vivo studies.3,4) Figure 1 schematically illustrates and compares the in vitro and in vivo skin dispositions of a drug and its metabolite after topical application. Overall skin permeations of the drug and its metabolites can be evaluated from the results of in vitro skin permeation experiments (Fig.…”
mentioning
confidence: 99%
“…Most drugs are taken up by these vessels to migrate to the systemic circulation, whereas a portion is further diffused into deeper tissues such as the subcutis and muscle. 1,2) If the applied drug is a prodrug, a peptide or an oligonucleotide that can be readily metabolized in skin, its metabolism makes the skin disposition of the drug very difficult.…”
mentioning
confidence: 99%